2018
DOI: 10.1002/mrm.27632
|View full text |Cite
|
Sign up to set email alerts
|

Mapping water exchange across the blood–brain barrier using 3D diffusion‐prepared arterial spin labeled perfusion MRI

Abstract: Purpose To present a novel MR pulse sequence and modeling algorithm to quantify the water exchange rate (kw) across the blood–brain barrier (BBB) without contrast, and to evaluate its clinical utility in a cohort of elderly subjects at risk of cerebral small vessel disease (SVD). Methods A diffusion preparation module with spoiling of non–Carr‐Purcell‐Meiboom‐Gill signals was integrated with pseudo‐continuous arterial spin labeling (pCASL) and 3D gradient and spin echo (GRASE) readout. The tissue/capillary fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
158
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(178 citation statements)
references
References 69 publications
3
158
0
1
Order By: Relevance
“…Mean ASL images were generated by a pairwise subtraction of the control and labeled images. The processing pipeline as seen in Figure 1 was used to determine cortical (11) ΔM = 2M 0 CBF exp −TI × R1 app exp (min (TI, + ) ΔR) − exp ( ΔR) ΔR (12) T w = − a F I G U R E 1 Processing pipeline to measure the exchange time (T w ) as an index of blood-brain barrier permeability to water using control data to determine extravascular tissue T 2 (T2 EV ), multiple-echo-time (multi-TE) arterial spin-labeling (ASL) data to determine intravascular/ extravascular ASL signal intensities (ΔM IV /ΔM EV ), intravascular T 2 (T2 IV ) and tissue transit time (δ), and multi-TI (inflow time) ASL data to determine arterial transit time (δ a ). Dotted lines indicate parameters with results for the individual animals and solid lines indicate parameters with result that is shared across the group.…”
Section: Data Processingmentioning
confidence: 99%
“…Mean ASL images were generated by a pairwise subtraction of the control and labeled images. The processing pipeline as seen in Figure 1 was used to determine cortical (11) ΔM = 2M 0 CBF exp −TI × R1 app exp (min (TI, + ) ΔR) − exp ( ΔR) ΔR (12) T w = − a F I G U R E 1 Processing pipeline to measure the exchange time (T w ) as an index of blood-brain barrier permeability to water using control data to determine extravascular tissue T 2 (T2 EV ), multiple-echo-time (multi-TE) arterial spin-labeling (ASL) data to determine intravascular/ extravascular ASL signal intensities (ΔM IV /ΔM EV ), intravascular T 2 (T2 IV ) and tissue transit time (δ), and multi-TI (inflow time) ASL data to determine arterial transit time (δ a ). Dotted lines indicate parameters with results for the individual animals and solid lines indicate parameters with result that is shared across the group.…”
Section: Data Processingmentioning
confidence: 99%
“…It should be noted that GBCA permeability reflects a fundamentally different aspect of BBB function (passive diffusion through intercellular pathways) compared to water permeability, which likely includes both passive (transcellular dominating intercellular) and active transport pathways 76 . Indeed, recent work has demonstrated that BBB water permeability measures can be obtained using noncontrast MRI techniques 77‐79 . Active water flux across the capillary endothelium is facilitated by transmembrane transporters and may provide high‐spatial resolution information on regional metabolic activity 75 …”
Section: Neuroinflammation Beyond Acute Contrast Enhancing Lesionsmentioning
confidence: 99%
“…Moreover, there is no need for further measurements with signalcrushing or diffusion-weighting gradients. 35 Common ASL quantities, such as ATT and CBF, can still be calculated from the acquired data. The main advantage of the concept is the fit stabilization based on external T 2,IV and T 2,EV estimates.…”
Section: Discussionmentioning
confidence: 99%